Educational responses to local and migration destination shocks: Evidence from China - Leight, Jessica; Pan, Yao (Oxford University Press, 2025)
Over the last 20 years, China has experienced substantial positive shocks to export-oriented industries—especially following its accession to the World Trade Organization—and these shocks have had major implications for human capital investment. One primary channel through which export expansion can shape choices about human capital accumulation is positive labor-demand shocks, and these shocks can be observed both at potential within-country migration destinations and in the locality of birth. Exploiting cross-county variation in the reduction in export tariff uncertainty post-WTO, both locally and at plausible migration destinations, this analysis finds that youth in China reaching matriculation age post-accession in counties experiencing a larger export shock (either locally or at those destinations) show a lower probability of enrolling in high school. This pattern is observed in a sample including both youth who ultimately migrate and youth who do not migrate. For urban youth, the effects of local shocks are larger than the effects of destination shocks, but the opposite pattern is observed for rural youth.